Optimization of Shatavari Powder Incorporation in Poultry Meat Nuggets - Sasi, Silpa; Sathu, T; C, Sunanda; M, Pavan; Vasudevan, V N; A, Irshad (Journal of Meat Science, 2025)
The present study was designed to determine the optimal concentration of Shatavari powder for integration into poultry meat nuggets. Various levels of Shatavari powder, at 0.5%, 1%, and 1.5%, were incorporated into the formulation of poultry meat nuggets, comprising 75% chicken and 25% duck meat, along with 2% jackfruit powder. Based on the sensory attributes, 0.5 percent shatavari powder was selected as the optimum level . Shatavari powder had a significant effect on the flavor, juiciness, texture, saltiness, and overall acceptability of the developed nuggets. The increase in levels of shatavari powder had an adverse effect on the sensory attributes due to the inherent bitter taste of the powder. The addition of shatavari powder at 0.5% in the nugget formulations was effective in sustaining the desired sensory attributes besides the nutritional benefits. Hence, acceptable functional nuggets can be made with the addition of shatavari powder up to two percent over and above the nuggets formulation containing 2 % jackfruit powder without affecting the sensory attributes.